Fake Smile Perspektif Hadis - Fathul Alwan Subandi; Masrukhin Muhsin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The phenomenon of the fake smile has become increasingly visible in the digital era, especially through social media platforms. Such expressions are often used to mask genuine emotions such as sadness, psychological pressure, or fatigue. This study examines how the Prophetic traditions (ḥadīth) address this phenomenon in relation to sincerity, ethical conduct, and emotional balance. Three research questions are posed: (1) whether ḥadīth encourage sincerity in smiling as an act of worship, (2) how fake smiles are situated within Islamic ethical perspectives, and (3) to what extent ḥadīth provide guidance for this issue in contemporary contexts. The study applies a qualitative method, employing library research and thematic analysis of ḥadīth (mawḍūʿī). Primary data are drawn from authoritative ḥadīth collections, while secondary sources include tafsīr, classical and modern commentaries, as well as psychological literature. The findings reveal that smiling is framed as a charitable act requiring sincerity. A fake smile intended to preserve harmony may still be valued positively, but one used for manipulation or to conceal hostility conflicts with the principle of truthfulness (ṣidq) and approaches hypocrisy (nifāq). The Prophet’s balanced expressions affirm the need for sincerity in social interaction.